A survey of East Palaearctic Gnaphosidae (Araneae). 10. Three new Gnaphosa species from the Dzhungarian Alatau Mountains (Eastern Kazakhstan) - Fomichev, Alexander A. (Zootaxa, 2019)
Three new species, Gnaphosa aksuensis sp. n., G. mataica sp. n., and G. prashkevichi sp. n., are described based on both sexes from Eastern Kazakhstan. Descriptions, illustrations, and maps showing records are provided. The new species represent a monophyletic rasnitsyni-group together with four Mongolian species.